Stem cell therapy for stroke - Parker, Graham C. (Journal of Pediatric Neurology, 2010)
Cerebral stroke can cause permanent neurological damage, behavioral incapacity and is associated with a high personal and financial cost. Therapeutic options are severely limited. In the past 10 years there has been an explosion of research interest in how a variety of stem cell populations respond in animal models of stroke. Manipulation of endogenous and exogenously introduced stem cells has provided a preponderance of information on how stem cells may improve aspects of cellular and functional recovery following largely ischemic models of stroke. These in turn have led the way to the initiation of clinical trials.
Keywords: Stem cells; therapy; stroke; cerebral ischemia